The impact of income taxation on the ratio between reservation and market wages and the incentives for labour supply - Marco Caliendo; Ludovica Gambaro; Peter Haan (Institute for the Study of Labor (IZA), 2007)
This paper extends previous research about the determinants of reservation wages by analysing the effect of progressive income taxation on the ratio between reservation and net market wages. Based on micro data for Germany (SOEP) we show that joint income taxation in Germany which discriminates by marital status, has a strong and highly significant impact on the reservation/market wage ratio. Relative to single filers, this leads to strong negative labour supply incentives for secondary earners and to positive incentives for first earners in married couples.
urn:nbn:de:101:1-20080422215
Keywords: 330; Einkommensteuer; Familienbesteuerung; Steuerwirkung; Anspruchslohn; Arbeitsangebot; Ökonomischer Anreiz; Frauenerwerbstätigkeit; Deutschland